Perlindungan Hukum Bagi Investor Pada Transaksi Aset Mata Uang Digital Cryptocurrency Di Indonesia - Gilang Prayoga, Agung; Nanang, Nanang (WELFARE STATE Jurnal Hukum, 2022)
Cryptocurrency or crypto currency is a digital currency that uses an encryption system and there are various forms of this digital currency spread all over the world. In Indonesia, people are starting to use Cryptocurrencies and not a few have become investors through this digital currency. The first problem How is the existence of cryptocurrency as a digital currency in Indonesia? Second, how is the legal power of cryptocurrency in Indonesia. This research method uses normative legal research methods. The result of the first discussion is that the existence of Cryptocurrency or cryptocurrencies only applies to the trading sector and is only recognized by Bappepti. The result of the second discussion is that cryptocurrency digital currency cannot be used as a legal currency because it does not meet the elements as a legal currency in Indonesia.